Euroscepticism Level of French Parties Determined by the Content-analysis of Their Pre-election Manifestos - A. O. DOMANOV (Ассоциация независимых экспертов «Центр изучения кризисного общества» (in English: Association for independent experts “Center for Crisis Society Studies”), 2018)
The dynamics of Euroscepticism intensity of some French parties is  analysed in the given article with the use of Attitude to European  integration index. The degree of criticism of the EU is evaluated  quantitatively (1-13 points) based on the following data extracted  from 2010-2017 party manifestos: attitude to the principal idea of European integration, affective and instrumental support or  discontent of the EU, the perception of the EU as an (un-)  accountable institution. The elaborated method was proven to be  instrumental and reliable for Euroscepticism studies by finding  correspondence between the quantitative values of the Index and  Russian scholars’ qualitative estimates. This standardized approach  to measurement allowed not only to reveal the general attitude of a  particular party towards European integration, but also to compare the obtained estimates with indicators for past years, for  other parties, and also in other countries. The developed scale let  ascertain some strengthening of National Front’s and J.-L.  Melenchon’s supporters’ (nowadays – from “Unbowed France”)  Euroscepticism and weakening criticism of the EU by gaullists from  the “Union for the Popular Movement” and the “Republicans”.  Relatively stronger Euroscepticism of the French Communist Party in  comparison to the Socialist Party has been confirmed.